Arbitraging Arbitrageurs - ATTARI, MUKARRAM; MELLO, ANTONIO S.; RUCKES, MARTIN E. (Journal of Finance, 2005)
ABSTRACT This paper develops a theory of strategic trading in markets with large arbitrageurs. If arbitrageurs are not well capitalized, capital constraints make their trades predictable. Other market participants can exploit this by trading against them. Competitors may find it optimal to lend to arbitrageurs that are financially fragile; additional capital makes the arbitrageurs more viable, and lenders can reap profits from trading against them for a longer time. The strategic behavior of these market participants has implications for the functioning of financial markets. Strategic trading may produce significant price distortions, increase price manipulation, and trigger forced liquidations of large traders.